The behavior of animals : mechanisms, function and evolution - Bolhuis, Johan J.; Giraldeau, Luc-Alain, 1955-; Hogan, Jerry A. (Hoboken, NJ : John Wiley & Sons, 2022)
"The idea for this book arose out of a need that we (and many of our colleagues) felt for a comprehensive textbook on animal behavior. There is no shortage of animal behavior textbooks, so why did we want to produce a new one? First, animal behavior is a dynamic field of research, and we believe that a modern textbook should incorporate all the contemporary subdisciplines of behavioral biology, such as animal welfare, evolutionary psychology, animal cognition, and behavioral neuroscience. In some ways, the science of animal behavior has become a victim of its own success, as it covers a much wider field than it did initially. Gone are the days when one author could write a textbook both comprehensive and authoritative: Robert Hinde's classic Animal Behaviour: A Synthesis of Ethology and Comparative Psychology (1970) is an outstanding example of such a book, and it continues to inspire many of us. Given the breadth of contemporary animal behavior research, we felt that it was important to invite experts in the respective subdisciplines to write a chapter about their specialist topic. Second, a large proportion of extant textbooks are single-author volumes that approach animal behavior from a particular perspective, for example from an evolutionary point of view or with the emphasis on mechanisms. We believe that a modern science of animal behavior should encompass both functional and causal approaches. For such a comprehensive approach, we found the classic formulation of the aims and methods of ethology (the study of animal behavior) by Niko Tinbergen, one of its founding fathers, most useful. Tinbergen suggested that there are four basic questions in animal behavior, namely about causation, development, survival value (function), and evolution. We agree with Tinbergen that all these four questions are equally important. Hence all of them are represented in this book. Like Tinbergen, we also find it important to distinguish among the four questions. In particular, it is important to realize which of the four questions is addressed, and to use a research approach appropriate for that question. Most chapters in the book focus on one of the four questions, with cause and development being the main subjects of the first ten chapters, and survival value (function) and evolution being the main subjects of the last seven chapters. But most chapters are also concerned with more than one question, noted separately of course, supporting Tinbergen's claim that all questions should be answered."--
Includes bibliographical references and index.
Keywords: Animal behavior; Conducta animal